Pelatihan Good Agricultural Practices (GAP) Tanaman Teh di KWT Turgo sebagai Tahap Awal Pembentukan Eduagrowisata - Yovi Avianto; Muhamad Fajar Sidiq; Muhammad Parikesit Wisnubroto; Yermia Prameswari (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2026)
The development of tea-based edu-agrotourism in Dusun Turgo requires a solid foundation in cultivation practices, well-organized plantations, and the capacity of the community to implement Good Agricultural Practices (GAP). This community service program aims to enhance the knowledge and skills of local residents regarding GAP for tea cultivation as an initial step toward establishing an educational, safe, and attractive edu-agrotourism area. The program was carried out participatively in Dusun Turgo, Purwobinangun Village, Pakem District, Sleman Regency, Special Region of Yogyakarta, through several stages: initial observation, needs assessment, preparation of training materials, extension activities, field demonstrations, cultivation practices, and evaluation. Data were collected using observations, pre-tests and post-tests, documentation, and brief interviews with participants. The results indicate an improvement in participants’ understanding of GAP principles, garden sanitation, pruning, plucking, and cultivation record-keeping. In addition, participants began to understand the relationship between a healthy, well-managed tea plantation and the learning experience of visitors. This program not only impacted cultivation aspects but also strengthened the community’s social and technical readiness toward edu-agrotourism development. It produced an initial training model based on plantation practices, community participation, and an educational tourism orientation that can be replicated in similar area development initiatives